Comparative immunity of antigen recognition, differentiation, and other functional molecules: similarities and differences among common marmosets, humans, and mice - Suzuki, Ryuji; Shiina, Takashi; Kametani, Yoshie; Sasaki, Erika; Habu, Sonoko (Experimental Animals, 2018)
The common marmoset (CM; Callithrix jacchus) is a small New World monkey with a high rate of pregnancy and is maintained in closed colonies as an experimental animal species. Although CMs are used for immunological research, such as studies of autoimmune disease and infectious disease, their immunological characteristics are less defined than those of other nonhuman primates. We and others have analyzed antigen recognition-related molecules, the development of hematopoietic stem cells (HSCs), and the molecules involved in the immune response. CMs systemically express Caja-G, a major histocompatibility complex class I molecule, and the ortholog of HLA-G, a suppressive nonclassical HLA class I molecule. HSCs express CD117, while CD34 is not essential for multipotency. CD117+ cells developed into all hematopoietic cell lineages, but compared with human HSCs, B cells did not extensively develop when HSCs were transplanted into an immunodeficient mouse. Although autoimmune models have been successfully established, sensitization of CMs with some bacteria induced a low protective immunity. In CMs, B cells were observed in the periphery, but IgG levels were very low compared with those in humans and mice. This evidence suggests that CM immunity is partially suppressed systemically. Such immune regulation might benefit pregnancy in CMs, which normally deliver dizygotic twins, the placentae of which are fused and the immune cells of which are mixed. In this review, we describe the CM immune system and discuss the possibility of using CMs as a model of human immunity.